Faktor-Faktor Preventif Obesitas pada Anak: Review - Rista Dwi Hermilasari (Program Studi Gizi UNSIKA, 2023)
Childhood obesity has become a health problem in the world because of the risk of developing chronic diseases. Children with obesity tend to experience premature death to a greater extent than children who are not obese. The main cause of obesity in children is diet accompanied by genetic, environmental and lifestyle factors. This review aims to determine the factors that play role in preventing obesity in children. The database sources used in the literature search were Google Scholar, PubMed, and Science Direct published in the last 5 years. Preventing obesity in children using a comprehensive intervention through family-based intervention, schools, dietary management and community-based intervention is important for fostering healthy living behavior to avoid the risk of metabolic disease. In the current technological era, implementing physical activity in children must be done from an early age. Keywords: Children, Intervention, Obesity